Do They Find You on Facebook? Facebook Profile Picture and Hiring Chances - Stijn Baert (Institute for the Study of Labor (IZA), 2015)
We investigate whether the publicly available information on Facebook about job applicants affects employers' hiring decisions. To this end, we conduct a field experiment in which fictitious job applications are sent to real job openings in Belgium. The only characteristic in which these candidates differ is the unique Facebook profile that can be found online with their name. Candidates with the most beneficial Facebook picture obtain approximately 39% more job interview invitations compared to candidates with the least beneficial picture. In addition, we find suggestive evidence for a higher effect of Facebook profile picture appearance on hiring chances when candidates are highly educated and when recruiters are female.
Keywords: C93; D83; J24; J79; L86; 330; hiring; screening; Facebook; Internet; personality; attractiveness